Globalisation processes and the labour market. Selected countries and aspects - Balcerowicz-Szkutnik, Maria (Procesy globalizacyjne a rynek pracy. Wybrane kraje i aspekty, 2015)
Changes of an economic, social and even political character are consequences of the process of globalisation that has been expanding for several recent decades. Changes in employment structure and thereby in the vision of the labour market are one of the results of this process. Changes of this type have their origins in modern technologies because they transform industrial civilisation into service civilisation. The scale of these changes indirectly depends on the potential of the labour resources occurring in local labour markets (they represent the whole countries). The paper focusses on analyses of the dynamics of changes in employment structures in major economy sectors in selected European Union states with a clear emphasis on Central and Eastern Europe in connection with changes in the consumption model approached as an echo of the globalisation processes
Ekonometria = Econometrics, 2015, Nr 4 (50), s. 24-42
Keywords: globalisation; servicisation; consumption model; labour market; globalizacja; serwicyzacja; model konsumpcji; rynek pracy